PENGARUH TERAPI AL-QUR’AN SURAH AR-RA’D AYAT 11 UNTUK MENINGKATKAN MOTIVASI BELAJAR MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 8 PEKANBARU - Siti Rahmawati; Tri Umari; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of group guidance through Al-Qur'an surah Ar-Ra'd verse 11 therapy to improve the learning motivation of XI grade students of Pekanbaru 8 High School in the academic year 2018/2019. The research design used was pre-experimental design with a single group initial-end test model. The research subjects in this study were 7 students from class XI Science 7 8Senior High School Pekanbaru who had low learning motivation. The instruments of data collection used in this study were learning motivation questionnaires in order to capture the subjects of research and observation in order to assess the implementation of group guidance. The data analysis technique used is the non parametrix statistical technique with the Wilcoxon test with the value of Asymp. Sig (2-tailed) = 0.018 <0.05 means that there are differences before treatment, namely 71% of students with learning motivation levels in the low category, and 29% of students in the very low category and after treatment there are 71% of students who have learning motivation moderate and the other 29% had high learning motivation and Rank Spearman test with Asymp. Sig (2-tailed) = 0.027 <0.05 means that there is an influence on the implementation of group guidance using Al-Qur'an therapy surah Ar-Ra'd to increase student learning motivation, then to determine the coefficient of determination as follows: (rs)2=(0,811) 2 = 0,657, meaning that the influence of group guidance using Al-Qur'an surah Ar-Ra'd therapy verse 11 to increase student motivation is equal to 65,7%.Key Words: Surah Ar-Ra'd Verse 11, Motivation Of Learning